(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
Sheep, camel wool, and woolen products are the main livestock products in Mongolia that satisfy population need and contribute certain amount of export revenue from international market. There is loss of possibility to produce ecologically clean safe, warm products [4] as only 10% of total wool is being processed. We tried to convince audience that it is required to support wool processing industry by right policy hence in ordinary weather conditions livestock number/ and wool production/ increases constantly and there are favorable circumstances established to supply products to China, Korea, South Eastern Asia and Russia with the ongoing process of market extension. DOI: http://dx.doi.org/10.5564/mjas.v11i2.231 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.120-124